Attention Manipulation for Naval Tactical Picture Compilation - Bosse, Tibor; Lambalgen, Rianne van; Maanen, Peter-Paul van; Treur, Jan (Proceedings of the 2009 IEEE/WIC/ACM International Joint Conference on Web Intelligence and Intelligent Agent Technology - Volume 02, 2009)
This paper discusses and evaluates an agent model that is able to manipulate the visual attention of a human, in order to support naval crew. The agent model consists of four submodels, including a model to reason about a subject’s attention. The model was evaluated based on a practical case study which was formally analysed and verified using automated checking tools. Results show how a human subject’s attention is manipulated by adjusting luminance, based on assessment of the subject’s attention. These first evaluations of the agent show a positive effect.